'Vaping' profiles and preferences: an online survey of electronic cigarette users. (28th March 2013) - Dawkins, Lynne; Turner, John; Roberts, Amanda; Soar, Kirstie
Abstract Aims To characterize e‐cigarette use, users and effects in a sample of Electronic Cigarette Company (TECC) and Totally Wicked E‐Liquid (TWEL) users. Design and setting Online survey hosted at the University of East London with links from TECC/TWEL websites from September 2011 to May 2012. Measurements Online questionnaire. Participants One thousand three hundred and forty‐seven respondents from 33 countries (72% European), mean age 43 years, 70% male, 96% Causacian, 44% educated to degree level or above. Findings Seventy‐four percent of participants reported not smoking for at least a few weeks since using the e‐cigarette and 70% reported reduced urge to smoke. Seventy‐two percent of participants used a 'tank' system, most commonly, the eGo‐C (23%). Mean duration of use was 10 months. Only 1% reported exclusive use of non‐nicotine (0 mg) containing liquid. E‐cigarettes were generally considered to be satisfying to use; elicit few side effects; be healthier than smoking; improve cough/breathing; and be associated with low levels of craving. Among ex‐smokers, 'time to first vape' was significantly longer than 'time to first cigarette' (t1104 = 11.16, P < 0.001) suggesting a lower level of dependence to e‐cigarettes. Ex‐smokers reported significantly greater reduction in craving than current smokers (χ21 = 133.66, P < 0.0007) although few other differences emerged between these groups. Compared with males, females opted more for chocolate/sweet flavours (χ21 = 16.16, P < 0.001) and liked the e‐cigarette because it resembles a cigarette (χ23 = 42.65, P < 0.001). Conclusions E‐cigarettes are used primarily for smoking cessation, but for a longer duration than nicotine replacement therapy, and users believe them to be safer than smoking.